A Novel Questionnaire Preparation of Construction Project - Subhan, Dr. M. D. (International Journal of Scientific Research in Civil Engineering, 2016)
Training needs analysis (TNA) determines the hole between ’what’s’ and ’what should be’ instances. Building enterprise is very most important for growth, progress and fiscal development of a nation and accordingly the assignment of analyzing training needs in construction tasks is very foremost side within the gift scenario of Indian development industry. Many of the building initiatives are pushing behind the schedule and coaching imparted to employees is just not established on systematic evaluation. On this gain knowledge of a model questionnaire has been all set which is distinct for the reason that questions related to training desires evaluation as well as reasons of prolong had been incorporated. The data so bought might be easy for evaluation and the outcome of hypothesis testing will likely be extra secure.